Low-Cost LoRa-Based IoT System for Automated Irrigation and Remote Monitoring in Family Horticulture - Caetano, Anne Karolyne; Oliveira, Julio Cesar S.; Pereira, Renata I. S.; Souza, Cleonilson P.; Jucá, Sandro C. S. (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2025: Anais do XVI Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2025)
This project developed a low-cost embedded system for automated irrigation and remote monitoring, based on IoT (Internet of Things) with LoRa communication, applied to family horticulture in Alagoas. The system enables remote monitoring of ambient and soil humidity and temperature without requiring Wi-Fi, making it ideal for rural areas. Collected data is sent to the cloud for analysis and control. An application was developed to facilitate farmers’ usage. The automation of irrigation reduces water waste and enhances agricultural productivity. Furthermore, the solution offers an excellent cost-benefit ratio, surpassing traditional market-available systems.